Cristalização hidrotérmica do gel de TiO2 obtido pelo método de decomposição de complexos e análise de suas propriedades fotocatalíticas - (:unkn) unknown (Universidade Federal de Goiás, 2018)
In recent years, titanium dioxide TiO2 has been well studied due to its various interesting physical and chemical properties, especially with regard to the application in processes of photocatalytic discoloration. These processes have always attracted the interest of the scientific community, mainly because it is possible to use sunlight as a source of energy for the reaction to happen. The present work had the objective of studying the influence of pH on the hydrothermal crystallization of the amorphous (TiO2) gel obtained by the complex decomposition method by two different routes varying temperature and time of synthesis, where in one of the routes the materials were crystallized in a reactor metal and on the other synthetic route was used a glass reactor. Such routes were used as a relatively new, promising and efficient processing method for obtaining this type of material. The obtained samples were characterized by different techniques: the X-ray diffraction confirmed the obtaining of monophasic materials and also in mixtures of phases, with tetragonal structure for the polymorphs anatase and rutile, proving that the hydrothermal method is efficient in the synthesis of the samples of interest having energy expenditure when compared to conventional crystallization methods. Using the X-ray diffraction data, the sizes of crystallites (TC), and the percentage values of phases present in each sample were measured. The (MEV/FEG) scanning electron microscopy characterization and (TEM) transmission, evidenced the changes in the size and morphology of the materials obtained, especially between anatase and rutile when single-phase. The photocatalytic tests showed the best performance of some materials, especially for the sample crystallized in pH 7 in the glass reactor, which decoloured the study dye in 99.7% due to its morphology as well as anatase / rutile composition in percentage terms.
Hydrothermal crystallization of TiO2 gel obtained by the method of complex decomposition and analysis of its photocatalytic properties
Keywords: Dióxido de titânio (TiO2); Cristalização hidrotérmica; Anatase; Rutilo; PH; Fotocatálise; Titanium dioxide (TiO2); Hydrothermal crystallization; Anatase; Rutile; PH; Photocatalysis; CIENCIAS EXATAS E DA TERRA::QUIMICA